HUBUNGAN PENGETAHUAN PASIEN DIABETES MELLITUS TIPE II DENGAN PRAKTIK PERAWATAN KAKI DALAM MENCEGAH LUKA DI WILAYAH KELURAHAN CENGKARENG - Wulandari Arifin, Nur Afni (Program Studi Ilmu Keperawatan, Fakultas Ilmu Kesehatan, Universitas Muhammadiyah Bengkulu, 2021)
The endocrine system controls the body's processes through chemicals, most of these chemicals are secreted in the glands. Endocrine glands are located throughout the body and each gland contains a special group of cells that secrete hormones directly into the bloodstream, circulated throughout the body. This hormone acts on distant tissues (called target tissue) via endocrine signals. Diabetic clients are very at risk for the incidence of preventing diabetic foot injury in diabetics with foot care. This study aims to determine the relationship between the knowledge of type II diabetes mellitus patients with daily foot care practices in preventing wounds. The many problems faced by diabetic clients, especially regarding foot care, can be prevented and minimized if clients carry out proper foot care knowledge and practices. This research is a quantitative study with a cross-sectional design and a sample size of 30 people. The results of the Chi-Square test analysis showed that there was a significant relationship between the knowledge of type II diabetes mellitus patients and the practice of foot care in preventing wounds (p = 0.020). Knowledge is very important in the actions of a person who practices foot care. Diabetic foot injury will not occur if people with diabetes have extensive knowledge and want to look after and want to take care of their feet regularly. Clients with diabetes mellitus must be aware that foot care activities are part of their daily habits. Therefore, it is necessary to develop health education on foot care and foot examination to minimize or prevent foot injuries in people with diabetes mellitus. So that cases of diabetic foot injury can be prevented from an early age.Keywords: Diabetes Mellitus Type II, Knowledge, Foot care